New Product Development at PT Asuka Engineering Indonesia - Elmira Salsabila; M. Jihadi M. Jihadi; Baroya Mila Shanty (Universitas muhammadiyah malang, 2022)
PT Asuka Engineering Indonesia is a company engaged in the construction sector, with electrical and instrumentation as their main services. The purpose of this study is to identify and analyze new products that are needed and desired by PT Asuka Engineering Indonesia's consumers. This research is an applied research with a qualitative approach. The analytical tool that used in this research is the New Product Development Stages. The result of this research is the discovery of an idea of new product that can be developed at the Asuka company, namely by adding services in information technology field. Suggestions from this research are that this can be a reference and input for companies to make decisions in developing new products in information technology field by pay more attention to consumer suggestions for new product requests as a consideration for products that should be developed.